EFFECT OF INSULIN ON LPS-INDUCED INFLAMMATORY MARKERS IN MOUSE COLON SMOOTH MUSCLE CELLS IN VITRO - Al-dwairi, Ahmed; Al-shboul, Othman; Alqudah, Mohammad; G Mustafa, Ayman; A Alfaqih, Mahmoud (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of the research is to determine the effect of supraphysiological doses of insulin on mouse colon smooth muscle cells (CSMCs) expression and secretion of pro-inflammatory cytokines interleukin 1 alpha (IL-1Î±) and tumor necrosis factor alpha (TNF-Î±) in vitro. Methods: Freshly isolated CSMCs from BALBc mice were cultured in Dulbecco's Modified Eagle Medium and treated with various doses of insulin (0, 1, 5, 10, and 20 nM) for 48 h, with/without lipopolysaccharides (LPS; 1 ug/mL) to induce inflammation. The levels of IL-1Î± and TNF-Î± in the cell homogenates and conditioned media were measured using ELISA. Results: Insulin alone (1, 5, 10, and 20 nM) did not elicit a significant change in the expression or secretion of IL-1Î± or TNF-Î± form CSMCs; however, insulin (10 and 20 nM) significantly (p<0.05) increased the expression and secretion (~1.3â€“1.6-fold) of both IL-1Î± and TNF-Î± from CSMCs in the presence of inflammatory stimulus LPS when compared to LPS alone. Conclusion: This study highlights the role of hyperinsulinemia on CSMC inflammation and its potential role in the pathogenesis of inflammatory bowel disease (IBD) during obesity. Measures that prevent obesity may protect against the development of IBD since the worldwide incidence of both obesity and IBD is increasing in a parallel fashion.